Alien hand syndrome – a rare presentation of stroke - Kelly Le; Christine Zhang; Lisa Greisman (Journal of Community Hospital Internal Medicine Perspectives, 2020)
Alien Hand Syndrome (AHS) is characterized by intermittent and involuntary movements of a single limb that is not associated with motor dysfunction. AHS may be the initial presentation of serious underlying pathology, such as stroke localized to the non-dominant parietal lobe, corpus callosum damage, or neurodegenerative disease. AHS occurs at a low prevalence in the general population yet represents significant underlying disease burden, necessitating early identification. In this case report, we present an 88-year-old right-handed male with involuntary movement of his left forearm and hand three hours prior to presentation. His symptom corresponded to findings on MRI of the brain, which showed acute infarcts of the right temporal lobe, right parietal cortex, and right parietal subcortex. Infarction of the right parietal cortex accounted for his AHS. The multifocal nature of the infarcts elevated the index of suspicion for an embolic source.